Indisciplina escolar: uma amostra de um caso do setor privado (uma escola do interior do Estado de São Paulo) - Caldeira, Uratã Alves [UNESP] (2009)
The present research is all about a study case using both quantitative and qualitative data. The main goal is to research the discipline problems that have shown up os in a private school from Piracicaba-SP, committed to a big private teaching franchising. We have been trying to check out which are the indiscipline problems that took place at this institutions during the year 2004, involving 7th and 8th grades of Grammar School; having in sight if there is any connection between the problems of behavior and socialeconomic, cultural and symbolic level of students and their families. The gathering of data related to indiscipline was made by means of documents that the school itself offerd so as to make it effective the control and institutional actions over the students. Concerning the social-economic and cultural level of students and families, we have used researches applied by the teaching system itself to which school is committed by contract and franchising. We could rather state that the most common problems found in documents are related to unappropriate talkings as well as delays to attend the classes on time, as if students rejected the present teaching standard despite valuing education seeing it as necessary for the accomplishmente of their professional and personal dreams.